Why Don't You Join In? A Typology of Information System Certification Adopters. (10th September 2020) - Lins, Sebastian; Kromat, Theresa; Löbbers, Julian; Benlian, Alexander; Sunyaev, Ali
ABSTRACT: While the importance of information system (IS) certifications to demonstrate compliance with security and personal data protection requirements is constantly increasing, competing (theoretical) viewpoints exist that outline the rationales for organizations to adopt certifications. The results of these competing perspectives are inconclusive research findings in the certification adoption literature. While organizations may use certifications to signal quality to consumers, others mainly adopt certifications to improve internal processes or create institutional legitimacy. To enhance our understanding of the motivation for online vendors to adopt IS certifications, we conduct a literature review and a ranking‐type Delphi study with two unique panels comprising certified online vendors ( N = 15 ) and certification authorities ( N = 24 ). As a result, we provide a rank‐order list of 24 motivators and 17 demotivators impacting online vendors' intentions to adopt IS certifications. We reveal that certain motives are context‐independent, whereas other motives are specific for electronic markets (e.g., "signal data protection"). We also provide rich descriptions of potential demotivators, thereby increasing our understanding of the boundary conditions for IS certification adoption. Comparing our findings to three competing theoretical perspectives enabled us to derive a typology of distinctive certification adopters: functionalists, institutionalists, and signalers. In developing this typology, our findings constitute a first step toward alleviating the inconclusive findings in the academic literature as well as highlighting differences in motivating and inhibiting factors that impact vendors' adoption intentions.